(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To determine people’s awareness, psyche, and behavior in preventing the Covid-19 epidemic using medical services at Thu Duc District Hospital from March to April 2020. Methods: form a descriptive cross-sectional study with a sample size including 437 people who came for medical examination and treatment at Thu Duc District Hospital from March to April 2020. The questionnaire developed by the research team was sent to the people via the Google Form application on mobile devices, the responses were recorded, processed, and analyzed on STATA software version 13.0. Results: 63.8% of people were concerned about the disease since the first cases were reported; 89.2% think the epidemic is very serious. The rate of general optimism about epidemic prevention and control is 64.3%, some content is not very optimistic: only 53.3% think that the current health system can manage when the epidemic spreads. 49.0% believe that the government will regulate the food problem well when the disease spreads. The majority of people well followed regulations on social distancing, the overall well behavior rate on Covid-19 prevention is 91.8%. Conclusion: People have high confidence in epidemic prevention and control ability but are less optimistic about the health system and controlling social factors if the disease spreads widely.